Does profitability affect stock prices? Empirical evidence from the plastic and packaging sub-sector of the Indonesia Stock Exchange - Apandi, Aden; Mustafa, Yusufi Arif; Kamilah, Siti; Amira, Siti (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
This study aims to analyze the effect of profitability ratios on stock prices of manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange (IDX) during 2019–2023. The profitability ratios examined are Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Using purposive sampling, five companies were selected, and secondary data were obtained from their annual financial reports. Data analysis was conducted through descriptive statistics, classical assumption tests, and panel data regression with the Random Effect Model (REM). The findings reveal that ROA and ROE have no significant effect on stock prices, while NPM has a positive and significant impact. These results indicate that investors tend to consider sales-based profitability rather than asset and equity efficiency when valuing stock prices in the plastic and packaging sub-sector. This study provides implications for investors, company management, and regulators in evaluating financial performance, formulating profitability strategies, and supporting capital market stability in Indonesia. Article Information:Received 7/10/2024 / Revised 11/12/2024 / Accepted 12/18/2024 / Online First 12/25/2024